Relação entre o risco de vulnerabilidade funcional com o nível de incapacidade em idosos com dor lombar crônica - Maria Carolina Viana Lemuchi (2024)
Introduction: Aging is a biological process that promotes functional decline but may increase vulnerability to acquire chronic diseases. The presence of chronic pain tends to make the elderly more vulnerable as it may reduce their functional capacity. Understanding the prognostic value of vulnerability in older adults with chronic lower back pain (CLBP) may be important for educating patients about the role of vulnerability in the clinical course of CLBP and also for identifying risk groups based on vulnerability levels. Objective: To compare the clinical presentation of older adults with CLBP classified into different vulnerability levels according to the CFVI-20 (low, moderate, and high vulnerability risk) and investigate whether vulnerability risk predicts functional disability in older adults with CLBP over a period of six months. Methods: This is an observational longitudinal study. Individuals with CLBP, aged 60 or older, of both sexes, were considered eligible for the study. Participants were assessed at 2 time points over a 6-month interval. At the initial assessment, collected data included sociodemographic and anthropometric characteristics, clinical information related to functional vulnerability (measured through the Clinical Functional Vulnerability Index), disability (measured through the Roland-Morris Disability Questionnaire), pain intensity, and kinesiophobia. At the 6-month follow-up assessment, information on disability was collected again. Multivariate linear regression analysis was used to identify the association of functional vulnerability risk (independent variable) with disability (dependent variable), after adjusting for covariates. Results: The study sample consisted of 118 participants, with 44.1% (n = 52) classified as low vulnerability risk, 39.8% (n = 47) with moderate risk, and 16.1% (n= 19) with high risk. The clinical presentation of the high vulnerability risk group showed higher kinesiophobia and disability than the low and moderate risk groups. The moderate-risk group showed higher disability than the low-risk group. Longitudinal analysis showed that vulnerability was not able to predict disability in older adults with CLBP over a 6-month period, after controlling the analysis for sex, body mass index, pain intensity, and kinesiophobia. The reduction in disability over the 6-month follow-up was similar across vulnerability risk groups. The mean differences between disability changes in the low vulnerability risk group compared to the moderate risk group were -0.3 (95% CI: -2.7; 2.2) points and compared to the high vulnerability risk group was -1.8 (95% CI: -5.2; 1.5) points. Conclusion: Older adults with CLBP who are more vulnerable presented clinically with higher levels of disability and kinesiophobia. However, vulnerability risk was not able to predict the level of disability over a 6-month follow-up.